2021
DOI: 10.3389/fcell.2021.639127
|View full text |Cite
|
Sign up to set email alerts
|

The Pharmacological Effect and Mechanism of Lanthanum Hydroxide on Vascular Calcification Caused by Chronic Renal Failure Hyperphosphatemia

Abstract: ObjectiveThe present work aimed to explore the efficacy of lanthanum hydroxide in managing the vascular calcification induced by hyperphosphate in chronic renal failure (CRF) as well as the underlying mechanism.MethodsRats were randomly allocated to five groups: normal diet control, CKD hyperphosphatemia model, CKD model treated with lanthanum hydroxide, CKD model receiving lanthanum carbonate treatment, together with CKD model receiving calcium carbonate treatment. The serum biochemical and kidney histopathol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…And lanthanum hydroxide delays the development of vascular calcification through inhibiting NF‐κB pathway activation via La 3+ . 27 In this study, we found that lanthanum hydroxide regulates the homeostasis of gut microbiota, affects amino acid metabolism, increases urinary ammonium circulation, and ultimately plays a role in kidney protection in CKD rat models.…”
Section: Introductionmentioning
confidence: 77%
“…And lanthanum hydroxide delays the development of vascular calcification through inhibiting NF‐κB pathway activation via La 3+ . 27 In this study, we found that lanthanum hydroxide regulates the homeostasis of gut microbiota, affects amino acid metabolism, increases urinary ammonium circulation, and ultimately plays a role in kidney protection in CKD rat models.…”
Section: Introductionmentioning
confidence: 77%
“…In adition, previous studies showed RANKL could promote the osteogenic differentiation and calci cation via the RANKL/RANK signaling pathway in VSMCs, which also could up-regulate the expression of Runx2 and OPN [24,25]. OPG can bind RANKL competitively to block the osteogenic differentiation and calci cation in VSMCs [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the osteogenic differentiation and calci cation in VSMCs(Figure 2), Runx2 is a key marker to drive this phenotypic differentiation, which is usually up-regulated during the osteogenic differentiation in VSMCs, promotes the expression of downstream osteogenic marker such as OPN, promotes the secretion of calci ed vesicles, and nally leads to the deposition of calcium-phosphate complexes in the vascular wall [26,27]. In adition, previous studies showed RANKL could promote the osteogenic differentiation and calci cation via the RANKL/RANK signaling pathway in VSMCs, which also could up-regulate the expression of Runx2 and OPN [24,25]. OPG can bind RANKL competitively to block the osteogenic differentiation and calci cation in VSMCs [24,25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lanthanum phosphate has low water solubility, does not pass easily through the intestinal wall, and can be excreted through the feces, thereby achieving the effect of alleviating renal failure in CKD rat models, decreasing serum phosphorus levels, and inhibiting vascular calcification, equivalent to the effects of lanthanum carbonate (LC). 15 , 16 ) LC has been used clinically and is regarded as safe, 17 ) so it is suggested that the safety of LH may also be good. Because of the long-term administration in our experiment, there is a very small amount of absorption of lanthanum ions.…”
Section: Introductionmentioning
confidence: 99%